Infection or affection: physical literacy and the reterritorialisation of the HPE curriculum. Issue 2 (4th May 2021) - Ovens, Alan; Enright, Eimear
ABSTRACT: Physical literacy has quickly become established within the broad fields of Sport, Health and Physical Education as a set of capabilities and dispositions that enable active participation in movement cultures across an individual's lifespan. In that sense, it has become a powerful concept in terms of being a desirable outcome of education programmes for young people in all spheres of their life as well as being a powerful discourse for sport and physical activity policy for all sectors of the community. Given this, the question arises as to its relationship with physical education, as a curriculum practice in schools. In this introduction to the special edition, we propose that the theoretical tools of assemblage and territorialisation provide a way to theorise curriculum and understand how the papers might be read with a sense of coherence. We conclude by suggesting that less focus needs to be paid to defining the essence and nature of physical literacy, and more attention given to how it potentially narrows the curriculum and more questioning of whose interests are being served by advocating for its uptake in HPE.